Wheat Genotypes as Affected by Terminal Heat Stress in Northern Bangladesh (Bangladesh Agronomy Journal, 2018)
This study was conducted in Crop Physiology and Ecology research field of Hajee Mohammad Danesh science and Technology University, Dinajpur during the two successive years of 2011-12 and 2012-13 to identify morpho-physiological attributes of wheat genotypes in response to terminal heat stress. In this respect, three sowing dates at November 27 (normal), December 17 (late) and January 7 (very late growing condition) and eight wheat genotypes viz., Pavon-76, Prodip, BARI Gom-25, BARI Gom-26, BAW-1143, BAW-1146, BAW-1147 and BAW-118 were evaluated. Growth and morphological changes of wheat genotypes were evaluated in relation to heat tolerance in field condition. Growth attributes such as LAR, SLA and LWR for all the genotypes declined throughout the advancement of growth stages in both the growing seasons and at heat stress condition values of all the parameters such as plant height and grain yields were reduced compared to normal condition.Bangladesh Agron. J. 2018, 21(1): 25-37